Quality Assessment on Generic Antipyretic Tablets and their Stability Withstanding Unfavourable Environments - Muhamad Syamir Anuar; Santhanathan S. Rajendram; Faizan Naeem Razali (Asian Journal of Medicine & Health Sciences, 2022)
Paracetamol is an antipyretic drug that is commonly used to lower body temperature. It is classified as an over-the-counter medicine and safe to be consumed with proper guidance. Paracetamol comes in many dosage forms, most commonly in tablet form. In this research, a comparison of two different brands of generic paracetamol tablets with a significant difference in selling price difference was evaluated. Two brands were tested, namely brand A and brand B, which passed the quality tests set by British Pharmacopoeia and United State Pharmacopeia in terms of the weight variation, friability, hardness test, disintegration, uniformity of thickness and dissolution. It was suggested that the cheaper paracetamol tablets (brand A) exhibited better quality as per the required standard. A stability study on the cheaper tablets (brand A) was also performed by manipulating the storage temperature of the tablet for a period of 30 days. The study revealed there were no significant quality changes when there was a change in storage temperatures. Overall, the study suggested that cheaper medication especially in tablet dosage form possessed excellent quality and appeared stable in different storage conditions. The present finding indirectly debunks the stigma that expensive medications are far better in terms of quality than the cheaper ones. Simultaneously, this will help in reducing the economic burden of patients from low- or middle-class income in finding suitable medication.